Effect of Lipid Ratio of Stearic Acid and Oleic Acid on Characteristics of Nanostructure Lipid Carrier (NLC) System of Diethylammonium Diclofenac - Hendradi, Esti; Rosita, Noorma; Rahmadhanniar, Erwinda (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2017)
The aim of this study was to determine the effect of lipid ratio of stearic acid and oleic acid on the physical characteristics as well as the entrapment efficiency of diethylammonium diclofenac with Nanostructure Lipid Carrier (NLC) system. Diethylammonium diclofenac (DETA) is Non-Steroid Anti-Inflamatory Drugs (NSAIDs) that has been widely used in the treatment of osteoarthritis and rheumatoid arthritis. In the formulation of NLC-DETA, three different lipid ratios were used, which the ratio of Â stearic acid:oleic acid were 60:40, 70:30, and 80:20, respectively. In this NLC system, DETA served as the active drug, stearic acid as solid lipid, oleic acid as liquid lipid, and Tween 80 as surfactant components. NLC were characterized for organoleptic characteristics, pH, viscosity, particle morphology, particle size and polydispersity index (PI), profiles of Fourier Transform Infra-Red (FTIR) and Differential Thermal Analysis (DTA), and drug entrapment efficiency. The particle shape and morphology were determined by Transmission Electron Microscopy (TEM). The results Â showed that the different ratios of oleic acid lipids and stearic acid had no significant effects on the viscosity and entrapment efficiency of NLC-DETA. On the other hand, it affected the pH of all formulas, which were significantly different. Increasing the amount of liquid lipid in the formulations reduced the size of NLC-DETA particles.Â